Unveiling the Dynamics of Household Poverty: Empirical Insights from a Developing Country. - Khan, Irum; Hasan, Hamid; Rehman, Hafiz Abdur (Journal of Poverty, 2026)
This study examines the determinants of poverty across all provinces using 2019–20 data from the Pakistan Social and Living Standards Measurement (PSLM) survey. The results from binary logistic regression analysis reveal several significant findings; household size, the square of the household head's age, marital status and province-specific factors are positively associated with a household head's classification as poor. Conversely, the age and gender of the household head, educational levels of the household head, household characteristics, and assets exhibit negative correlations with poverty. The findings will offer valuable insights for policymakers to formulate targeted poverty reduction strategies toward potential solutions.